ON TOPOLOGICALLY ζ-TRANSITIVE MAPS - KHALAT, DILSHAD J.; KHALAF , ALIAS B. (Journal of Duhok University, 2023)
In this paper, we describe and investigate some of properties of a new type of topologically transitive maps called topologically -transitive in a topological space  via the concept of -open sets. Some properties of these maps are given and relation among topological transitivity, topological -transitivity and topological -transitivity are discussed